Positive solutions of a three point boundary value problem - Webb, J.R.L. (Нелинейные граничные задачи, 2000)
We establish existence of positive solutions of some boundary value problems for a second order semilinear ordinary differential equation u" + g(t)f(u) = 0 on [0,1]. The boundary conditions involve three points, 0 ‹ η ‹ 1. The conditions on f strictly include the sub- and super-linear cases.